The association between anticipatory appraisals and affective reactivity - Kinnear, Lana Bernasek, author; Luong, Gloria, advisor; Lucas-Thompson, Rachel, committee member; Pena, Anita, committee member (Colorado State University. Libraries, 2025)
Stressors are challenging and sometimes threatening events. Exposure to stressors can lead to decreases in positive emotions and increases in negative emotions, referred to as positive and negative affective reactivity, respectively (Luong et al., 2023). People can differ in affect reactivity, even when they face the same stressor. One possible explanation for such individual differences is that they may differ in their appraisals or evaluations of the stressors (Boeninger et al., 2009). For example, anticipatory appraisals are the evaluations or perceptions of how pleasant or unpleasant an upcoming stressor or event will be (Gaab et al., 2005). Yet, it is unclear whether more positive anticipatory appraisals are associated with greater or less affective reactivity. Past research has largely focused on anticipatory appraisals after individuals were introduced to a stressor and had some knowledge of the stressor characteristics, but before the stressor had occurred. Less work has focused on how positive anticipatory appraisals may shape affective reactivity when the characteristics of an upcoming stressor are unknown or ambiguous in nature, though some findings have suggested that being overly positive may lead to greater affective reactivity when expectations are not met (i.e., a stressor is more negative or threatening than initially evaluated; Sweeny & Andrews, 2017; Sweeny & Shepperd, 2010). The current study leveraged data from 157 participants in the Health and Daily Experiences (HEADE) study to examine the impact of positive anticipatory appraisals on affective reactivity following exposure to a well validated lab stressor known as the Trier Social Stress Test (TSST). Participants completed semi-random daily life ecological momentary assessment (EMA) surveys. These EMA surveys included questions on anticipatory appraisals of the upcoming lab session before participants had full knowledge of what to expect, only that they would complete cognitive tasks in the lab. It was hypothesized that more positive anticipatory appraisals would predict greater positive and greater negative affective reactivity. Multiple regression analyses showed that more positive anticipatory appraisals were associated with greater positive affective reactivity, but not negative affective reactivity. These findings highlight the need for more research on the influence of anticipatory appraisals of an ambiguous stressor on affective reactivity.
Keywords: appraisals; affective reactivity; emotions